Performance of Multi Server Validation and Key Association with User Protection in Network Security (International Journal of Engineering and Computer Science, 2018)
The use of smart cards, far off person validation and key association can be simplified, bendy, and efficient for growing a comfy allotted computer systems surroundings. Addition to user authentication and key distribution, it is very useful for providing identification privacy for users. on this paper, we propose novel multi server authentication and key agreement schemes with consumer protection in community protection. We first endorse a single-server scheme and then observe this scheme to a multi-server environment. the principle deserves. Encompass: (1) The privacy of users may be ensured; (2) a consumer can freely choose his own password; (3) the computation and conversation price could be very low; (4) servers and users can authenticate every other; (five) it generates a consultation key agreed with the aid of the server and the person; (6) our proposed schemes are Nonce-based schemes which does now not have a serious time synchronization problem.